Recent technological innovations in mycelium materials as leather substitutes: a patent review - Elsacker, Elise; Vandelook, Simon; Peeters, Eveline (Frontiers in Bioengineering and Biotechnology, 2023)
Leathery mycelium materials, made from the vegetative part of filamentous fungi, have garnered significant interest in recent years due to their great potential of providing environmentally sustainable alternatives to animal- and plastic-based leathers. In this systematic patent review, we provide an in-depth overview of the fabrication methods for mycelium materials as leather substitutes recently described in patents. This overview includes strategies for fungal biomass generation and industrial developments in the sector. We discuss the use of various fungal species, plasticizers, crosslinking agents, and post-processing techniques, thereby highlighting potential gaps in scientific knowledge and identifying opportunities, challenges, and concerns in the field. Our analysis suggests that mycelium materials have significant potential for commercialization, with a growing number of companies betting on this new class of biomaterials. However, we also reveal the need for further scientific research to fully understand the properties of these materials and to unlock potential applications. Overall, this patent review delineates the current state of the art in leathery mycelium materials.